Foreign aid and political instability in resource-rich countries. (October 2018) - Ravetti, Chiara; Sarr, Mare; Swanson, Tim
Abstract: In this article we examine whether foreign aid and natural resources can act as a double curse on developing countries with poor governance. We hypothesize that affording external liquidity to dictators based on their resource wealth reduces the political incentives for long term investment and enhances the looting of the country and more frequent irregular exit of leaders from their office. We then examine the empirical evidence for such a link between international aid flows and government irregular turnover in resource-rich countries. We find that the interaction between natural resources and most forms of international aid combines with political instability in the case of non-democratic regimes. In turn, this combination of foreign aid, natural resources and political instability is associated with lower growth performance. Some types of less fungible aid (notably humanitarian) and aid grants that do not build indebtedness do not seem to have this effect. Abstract : Highlights: We develop a theoretical model for the double-curse of aid liquidity to resource rich autocracies. Insecurity in tenure of dictators and the use of resources as a collateral underlies the political economy issue with aid. The interaction between resources and some forms of aid correlates with political instability, particularly in non-democratic regimes. Foreign aid combined with natural resources and political instability is also associated with lower growth performance. Some types of government aid (notably humanitarian aid or grants) do not have this effect.